2002
DOI: 10.1002/jemt.10240
|View full text |Cite
|
Sign up to set email alerts
|

Genetic abnormalities of the endothelium

Abstract: Endothelial cell dysfunction plays an important role in the development and progression of cardiovascular and other disease. The purpose of this review is to discuss some of the genetic diseases known to adversely affect endothelial function. Although the list is exhaustive, we focus our discussion on primary pulmonary hypertension, diabetes mellitus, Alzheimer's disease, Crohn's disease, Von-Hippel-Lindau disease, familial Mediterranean fever, thrombotic microangiopathy, and key vascular malformations. Endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…First isolated, purified, and sequenced in 1988 [41], in health, the production of ET-1 is minimal and it is effectively opposed by NO and other endothelium derived vasodilators [42]. The circulating level of this short peptide was quickly determinant in humans and it was reported that, in most cardiovascular diseases, circulating level of ET-1 was increased [43].…”
Section: Morphological and Structural Features Of Endotheliummentioning
confidence: 99%
See 3 more Smart Citations
“…First isolated, purified, and sequenced in 1988 [41], in health, the production of ET-1 is minimal and it is effectively opposed by NO and other endothelium derived vasodilators [42]. The circulating level of this short peptide was quickly determinant in humans and it was reported that, in most cardiovascular diseases, circulating level of ET-1 was increased [43].…”
Section: Morphological and Structural Features Of Endotheliummentioning
confidence: 99%
“…Endothelial dysfunction is known to be implicated in the pathogenesis and clinical course of all known cardiovascular diseases [136, 137], occurs in response to cardiovascular risk factors, and precedes the development of atherosclerosis [42, 138, 139]. Endothelial dysfunction actively participates in the process of lesion formation promoting the early and late mechanisms of atherosclerosis [32, 40, 42], determining increase in EC permeability, upregulation of adhesion molecules, chemokine and cytokine secretion, and leukocyte adherence, enhanced oxidized-low density lipoprotein (ox-LDL), platelet activation, and vascular smooth muscle cell proliferation and migration.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the endothelium deteriorates or becomes dysfunctional, blood flow is disturbed and vessels become obstructed, leading to ischemia of downstream organs including the heart [66–71]. Endothelial damage is associated with most forms of CVD, including hypertension, coronary artery disease, CHF, peripheral artery disease, diabetes, chronic renal failure, and pulmonary hypertension [7276]. Endothelial function is altered in the presence of cardiovascular risk factors, suggesting that endothelial dysfunction is likely to be an important first step in CVD [7786].…”
Section: Vascular No Formationmentioning
confidence: 99%